Accordi spagnoli con la Chiesa cattolica. Dubbi di costituzionalità e necessità di modifiche (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Costituzione, neutralità e cooperazione - 2. La nomina degli arcivescovi, vescovi e coadiutori - 3. Nomina del vicariato militare - 4. Notifica della denuncia di azioni criminali - 5. Autonomia della Chiesa e diritti fondamentali dei suoi fedeli - 6. Assistenza religiosa - 7. Insegnamento della religione cattolica - 8. Creazione e gestione delle università cattoliche - 9. Finanziamento sulla base dell’IRPEF - 10. Finanziamento indiretto - 11. Alcune conclusioni.Agreements between Spain and the Holy See. Doubts about their constitutionality and need for changeABSTRACT: The Agreements between Spain and the Holy See were signed forty years ago, and there are still doubts about their constitutionality. This paper studies the main topics related to the agreements from the constitutional perspective: the participation of the head of the State in the appointment of bishops (particularly the Military Vicar General); the teaching of the Catholic religion in the public school; the Catholic military chaplains in the armed forces; or the public financing of the Catholic Church through the personal income tax. Finally, the paper analyzes the agreements as a technique of cooperation between the State and the Catholic Church.